A novel SEMA6B variant causes adult-onset progressive myoclonic epilepsy-11 in a Chinese family: A case report and literature review - Chen, Yirao; Yang, Xingyan; Yan, Xinxiang; Shen, Lu; Guo, Jifeng; Xu, Qian (Frontiers in Genetics, 2023)
This study describes a patient with progressive myoclonic epilepsy-11 (EPM-11), which follows autosomal dominant inheritance caused by a novel SEMA6B variant. Most patients develop this disease during infancy or adolescence with action myoclonus, generalized tonic-clonic seizures (GTCS), and progressive neurological deterioration. No cases of adult-onset EPM-11 have been reported yet. Here, we present one case of adult-onset EPM-11 who experienced gait instability, seizures, and cognitive impairment, and harbored a novel missense variant, c.432C>G (p.C144W). Our findings provide a foundation for a better understanding of the phenotypic and genotypic profiles of EPM-11. Further functional studies are recommended to elucidate the pathogenesis of this disease.